Examining the Role of AI-Powered Writing Assistants in Enhancing Critical Thinking In EFL Academic Writing - Tahir, Muhammad; Jahrir, Andi Sahtiani; Asrifan, Andi; Ariatna, Ariatna (JOLLT Journal of Languages and Language Teaching, 2025)
AI-driven writing assistants in EFL classrooms have revolutionized academic writing pedagogy, offering students immediate feedback on grammar, coherence, and organization. Although AI tools have demonstrated efficacy in improving linguistic precision, their influence on developing critical thinking remains ambiguous, especially among varying competency levels. Current study predominantly emphasizes AI’s impact on grammatical corrections, although there is a paucity of knowledge on its effect on higher-order cognitive involvement, including argumentation and reasoning abilities. This study examines the interaction between EFL students and AI feedback, assessing its impact on promoting or obstructing critical thinking. The study reveals that, through examining pre-test and post-test writing evaluations, student reflections, and AI feedback patterns, lower-proficiency students (B1) predominantly depend on AI for superficial adjustments. In contrast, advanced learners (C1) interact with AI-generated ideas more critically. Nonetheless, AI’s constraints in assessing argument strength and logical reasoning demonstrate that it cannot entirely supplant human feedback. These findings indicate that AI should be deliberately integrated with teacher support to optimize its advantages while reducing over-dependence. Future studies should investigate AI-human hybrid feedback models to improve language proficiency and critical thinking skills in academic writing.